Utilization of Liquid Organic Fertilizer of Pineapple Peel Waste for Shallots Cultivation (Allium ascalonicum L.) - Esa Frilian Cristina; Ismed Inonu; Nyayu Siti Khodijah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
Pineapple peel waste can be used as liquid organic fertilizer (LOF) to add organic matter and improve soil quality for cultivating crops such as shallots. Shallots re vegetable crops that have great prospects for farmers because of the high demand for shallots that were not in accordance with their production. This study aimed to determine the effect of concentration and frequency of application of LOF of pineapple peel waste on the growth and yield of shallots. This research had conducted in farmer’s land in Perlang Village, Lubuk Besar District, Central Bangka Regency, from January to April 2021. This research used experimental method with a split plot design. The main plot is the concentration of LOF of pineapple peel waste which consists of 30 ml/l and 60 ml/l. Sub-plots are the frequency of application LOF of pineapple peel waste which consists of once in 7 days, once in 14 days, and once in 21 days. The results showed that the concentration of LOF of pineapple peel waste had no significant effect on all observed variables. The frequency of application LOF pineapple peel waste had a significant effect on the number of tillers per clump, but had no significant effect on the other variables. The interaction between the concentration and frequency LOF pineapple peel waste had no significant effect on the growth and yield of shallot plants. LOF application of pineapple peel waste with a concentration of 30 ml/l and a frequency of once every 7 days tends to be better for the growth and yield of shallot plants.